Spontaneous spiking and synaptic depression underlie noradrenergic control of feed-forward inhibition - Kuo, Sidney P. (2011)
Inhibitory interneurons across diverse brain regions commonly exhibit spontaneous spiking activity, even in the absence of external stimuli. It is not well understood how stimulus-evoked inhibition can be distinguished from background inhibition arising from spontaneous firing. We found that noradrenaline simultaneously reduced spontaneous inhibitory inputs and enhanced evoked inhibitory currents recorded from principal neurons of the mouse dorsal cochlear nucleus (DCN). Together, these effects produced a large increase in signal-to-noise ratio for stimulus-evoked inhibition. Surprisingly, the opposing effects on background and evoked currents could both be attributed to noradrenergic silencing of spontaneous spiking in glycinergic interneurons. During spontaneous firing, glycine release was decreased due to strong short-term depression. Elimination of background spiking relieved inhibitory synapses from depression and thereby enhanced stimulus-evoked inhibition. Our findings illustrate a simple yet powerful neuromodulatory mechanism to shift the balance between background and stimulus-evoked signals.